Pituitary Adenoma: Early Results after Gamma Knife Radiosurgery in Iran - Oraee Yazdani, Saeed; Zali, Alireza; Shahrzadi, Sohrab; Alikhani, Mazdak; Tabatabaei, Seyed Morteza (International Clinical Neuroscience Journal, 2016)
Purpose: To study early treatment outcomes and complications of Gamma Knife Radiosurgery (GKRS) in patients with functional and nonfunctional adenomas. Methods: One hundred patients with a pituitary adenoma who were treated between 2011 and 2014 at Iran Gamma Knife Center were studied. The patients were followed up at least 2 years. Radiosurgery was performed using the Leksell Gamma Unit. The median radiation dose was 18 Gy for non-functional and 24 Gy for functional adenoma. The MRI were compared pre and post operation for any change in tumor size. Endocrine follow up was used to determine the onset of new hormone deficiency when available or decrease in hormonal level. Results: Our study group comprised 42 men (42%) and 58 women (58%). Ninety-three patients were treated for recurrent or residual disease after Trans-sphenoidal surgery or craniotomy and 7 patients were treated as primary modality because of extensive involvement of cavernous sinus or high risk for surgery. Forty-six patients (46%) had a diagnosis nonfunctional and 54 of patients (54%) had hormone-secreting tumors including growth hormone secreting (23%), prolactinoma (15%) and ACTH-secreting tumor (6%). No mortality was reported. Acute complication was uncommon and of no clinical significance. Late complication was noted in two patients (2%) and consisted of VI cranial nerve palsy with spontaneous resolution. None of the patients developed visual loss. Before GKRS, 8 patients had cranial nerve palsy. After the treatment, the palsy resolved in six (75%) of these patients. Only 9.5% of patients developed hypopituitarism and required replacement therapy. Overall control was 92% (28% decreased in volume and 64% were unchanged), 8% experienced an increase in volume size. Normalization of GH and IGF-1 for GH-secreting hormone was 48% with overall control of 73%. PRL normalization for prolactinoma was 46% with overall control of 67%. ACTH normalization for ACTH-secreting hormone was 35% with overall control of 70%. Conclusion: It seems that GKRS to be safe and effective method for tumor control and optimal hormonal function.